Mycoremediation of Endosulfan and Its Metabolites in Aqueous Medium and Soil by Botryosphaeria laricina JAS6 and Aspergillus tamarii JAS9 - Silambarasan, Sivagnanam (Public Library of Science, 2013)
Microbial degradation offers an efficient and ecofriendly approach to remove toxicants from the contaminated environments. Botryosphaeria laricina JAS6 and Aspergillus tamarii JAS9 were capable of degrading endosulfan and their metabolites which were isolated through enrichment technique. Both the strains were able to withstand an exposure of 1300 mg/L and showed luxuriant growth at 1000 mg/L of endosulfan. The change in pH in the culture broth was from 6.8 to 3.4 and 3.8 during growth kinetic studies of JAS6 and JAS9 strains, respectively upon biological degradation of endosulfan. The degradation of endosulfan by JAS6 and JAS9 strains were examined by HPLC. The biodegradation rate constant (k) and the initial concentration were reduced by 50% (DT(50)) which was determined by first and pseudo first order kinetic models. In the present investigation it has been revealed that Botryosphaeria laricina JAS6 and Aspergillus tamarii JAS9 possessing endosulfan degrading capability are being reported for the first time. These findings confirm the degradation of endosulfan by JAS6 and JAS9 strains which were accompanied by significant reduction in the toxicity and could be used as remedial measure in contaminated environments.